GUIDELINES FOR DEVELOPING LOCAL ADMINISTRATIVE ORGANIZATIONS INTO “SMART CITIES” - Ueafue, Chao; Sonchai, Arun; Kitjarak, Teeraphat; Tritose, Supachai; Lanchan, Ongaaj (Journal of MCU Nakhondhat, 2025)
Local government organizations are organizations that provide public services for the benefit of local people based on the principles of sustainable development. Good local administration requires highly professional executives and civil servants, adhering to the principles of fast, precise work, and supporting the diversity of local contexts under the participation and cooperation between the government sector, private sector, civil society, and the public in determining the appropriate direction of local development. This academic article is a documentary study with the objective of studying the development guidelines for local government organizations to become “smart cities” and presenting concepts, methods, and guidelines for developing local government organizations into “smart cities” in various forms through perspectives based on concepts and theories about smart cities. Concepts and theories about local government organizations and smart city development are processes that require cooperation from all sectors. Incorporating technology into management will help increase service efficiency and create sustainable satisfaction for local people. The study found that the development guidelines for local government organizations to become “smart cities” include: 1) Application of information technology, such as using information systems for effective planning and decision-making, developing applications to provide services to the public quickly and conveniently; 2) Improving work processes, such as reducing unnecessary steps to increase service efficiency, training personnel to have knowledge and skills in using new technologies; 3) Creating transparency and accountability, such as disclosing information about the organization’s work and spending to the public. Promote public participation in monitoring and providing suggestions to organizations.